2004
DOI: 10.1021/jm049486a
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of N-(2-Chloro-6-methyl- phenyl)-2-(6-(4-(2-hydroxyethyl)- piperazin-1-yl)-2-methylpyrimidin-4- ylamino)thiazole-5-carboxamide (BMS-354825), a Dual Src/Abl Kinase Inhibitor with Potent Antitumor Activity in Preclinical Assays

Abstract: A series of substituted 2-(aminopyridyl)- and 2-(aminopyrimidinyl)thiazole-5-carboxamides was identified as potent Src/Abl kinase inhibitors with excellent antiproliferative activity against hematological and solid tumor cell lines. Compound 13 was orally active in a K562 xenograft model of chronic myelogenous leukemia (CML), demonstrating complete tumor regressions and low toxicity at multiple dose levels. On the basis of its robust in vivo activity and favorable pharmacokinetic profile, 13 was selected for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
927
2
11

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,208 publications
(968 citation statements)
references
References 8 publications
28
927
2
11
Order By: Relevance
“…2D-DIGE is now recognized as an extremely robust method in comparative proteomics to analyse and detect changes related to a variety of effects on the cellular proteome. Dasatinib, a multi-target tyrosine kinase inhibitor, has activity against several kinases including BCR-Abl, SRC kinases, C-Kit, PDGFR, and ephrin-A receptor kinases [6]. In preclinical studies, dasatinib has shown good anti-proliferative and antiinvasive effects in melanoma cell lines [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2D-DIGE is now recognized as an extremely robust method in comparative proteomics to analyse and detect changes related to a variety of effects on the cellular proteome. Dasatinib, a multi-target tyrosine kinase inhibitor, has activity against several kinases including BCR-Abl, SRC kinases, C-Kit, PDGFR, and ephrin-A receptor kinases [6]. In preclinical studies, dasatinib has shown good anti-proliferative and antiinvasive effects in melanoma cell lines [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Dasatinib is a potent inhibitor of BCR-Abl, SRC kinases, C-Kit, PDGFR, and ephrin-A receptor kinases [6], with an IC 50 of 0.5 nM for SRC (IC 50 of <30 nM for the other targets) [6]. It has shown good pre-clinical activity in several cancer types including melanoma, breast, and colon cancer [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Animals were randomly assigned to three groups: Group 1 received treatment by daily gavage with 1.6 mg dasatinib (equivalent to approximately 5 mg/kg; n ¼ 18) in 10% DMSO/90% polyethylene glycol (PEG) 300 vehicle (n ¼ 18), a dose previously shown to inhibit tumor growth in vivo (1) ; group 2 received vehicle alone by daily gavage (n ¼ 18); and group 3 received a subcutaneous injection with zoledronic acid (100 mg/kg) on day 0 and at 6 weeks (n ¼ 4). (26) After 4, 8, and 12 weeks of treatment, six animals each from the vehicle and dasatinib groups were culled for sera, mCT, and histologic analysis.…”
Section: Experimental Designmentioning
confidence: 99%
“…Dasatinib (Sprycel) is a novel, orally available, multitargeted, potent tyrosine kinase inhibitor that inhibits several critical oncogenic proteins, including BCR-ABL, SRC family kinases, c-KIT, PDGFR and ephrin A receptor kinase (Lombardo et al, 2004;Lee et al, 2005;Nam et al, 2005;Schittenhelm et al, 2006;Wang et al, 2007). Dasatinib has the greatest potency among the second-and third-generation tyrosine kinase inhibitors in vitro against ABL kinase activity (O' Hare et al, 2005;Quintas-Cardama et al, 2006), being 325-fold more potent than imatinib and 16-fold more potent than Therapeutic strategies for MPD C Kumar et al nilotinib.…”
Section: Ph( þ ) Mpd: CMLmentioning
confidence: 99%